Vorbildhaftes Gottvertrauen: der matthäische Jesus zwischen tödlicher Ohnmacht und königlicher Macht - Blumenthal, Christian (Biblica, 2018)
Contrary to Markan Christology, Matthew emphasises the kingly-davidic identity of Jesus and develops this motif throughout his narrative. The paper concentrates on the depiction of Jesus as kingly figure during his journey, as narrated in Mt 16:21-20:34. Particularly, the chief characteristics of power and powerlessness as well as their theocentric foundation are central aspects for the portrayal of Jesus. Furthermore, Jesus functions as an example for the Matthean community. In conjunction with God and Jesus, this community is called to help establish the heavenly kingdom on earth.